A Sociolinguistic Analysis of Language Variation in Private and Government Schools of Pakistan - Anwar, Nazia; Malik, Moazzam Ali; Butt, Isha Razzaq (Pakistan Languages and Humanities Review, 2025)
The current research aims to study the linguistic variation among the students of the private and government schools in District Gujrat, Punjab, Pakistan to examine how social, cultural and attitudinal aspects affect language usage among the students. Based on sociolinguistic and variationist approaches, the study investigates the variation in English, Urdu and Punjabi use in two sectors of education which are reflecting different social classes and pedagogical orientations. A mixed methodology was used which included quantitative study of speech samples and questionnaires of 200 students and qualitative data of 24 semi-structured interviews. The results show that students in the private schools are more fluent and more frequent in using English, they use code-switching more frequently and more aware of language prestige, whereas students in the government schools use Urdu and Punjabi as their major languages with a sense of formality and limited access to English. The research concludes that linguistic competence and identity formation is influenced by the medium of education, exposure, and institutional attitudes. These trends indicate wider social inequalities and symbolic authority of English in the stratified educational system in Pakistan. The study recommends the necessity to implement equal bilingual policies and equal language resources to decrease linguistic and educational inequalities.